Modeling the potential distribution to present and future of the poorly known species Xenohyla eugenioi Caramaschi, 1998 (Anura: Hylidae) with findings about its distribution, natural history, and conservation - Andrade, Hugo; Dias, Eduardo José dos Reis; Almeida, Rony Peterson Santos; Costa, Bruno Bove da; Neves, Matheus Oliveira (Papéis Avulsos de Zoologia, 2024)
The distribution of anurans is conditioned by historical factors and ecological drivers. Thus, Species Distribution Models are important tools to provide information on the potential distribution of the species and determine where they will be requirements in future. Here our aim was modeling the current and future distribution and discussing about conservation of Xenohyla eugenioi. We searched for occurrence records through literature and scientific collections data. This species has approximately 650 km in straight line between the extreme localities, occurring mainly in bromeliads near to water bodies. he Ensemble method indicates the most probable areas of occurrence were over ecotonal range between Caatinga and Atlantic Forest and our projections have showed suitable conditions to highlands (up to 1.000 m). While, in the future, is expected erosion of the X. eugenioi populations, due climatic changes, which reinforce the caution to conservation of this poorly known species and necessity of studies about its ecology, natural history and distribution. Moreover, we hope that this work will contribute to the discovery of new records, characterizing the narrower niche space than this species may actually inhabit.